SABAH DI TENGAH PROSES DEKOLONISASI DI ASIA TENGGARA (1957-1968) - Pradadimara, Dias Pradadimara (Universitas Hasanuddin, 2014)
This paper is a review on the ways in which the issue of Sabah‘s status was being raised at thesame time as the birth of Malaysia and the objection of the Philippines over the inclusion ofSabah into the newly born nation-state, and how Indonesia with their own territorial problemsespecially over West Irian/ Papua was dragged in it. The dispute over Sabah (which until 1963was called as North Borneo) was part of the birth of the Malaysian Federation. The ―SabahQuestion‖ has indeed not been resolved. This issues seems to be deliberately forgotten both byMalaysia and by the Philippines, elthough for different reasons. What happened on February2013 in Sabah seems to force both sides to remember the past to find a way out.Keywords: Sabah—decolonization—Southeast Asia—dispute—history